ANALISIS PENGARUH FAKTOR KARAKTERISTIK KEPRIBADIAN TERHADAP KINERJA KARYAWAN - Mahmudatul Himma; Muhamad Muwidha (Adbis: Jurnal Administrasi dan Bisnis, 2019)
This research aimed is knowing and analyzing the effect of personality character on the employees’performance in PT PembangkitanJawa – Bali Unit Pembangkitan Brantas Karangkates. The data were collected through observation, questionnaires, interviews and documentation of employees in PT Pembangkitan Jawa – Bali Unit Pembangkitan Brantas of human resources with 28 employees as the sample. The analysis used simple inear regression. The results of the study show that personality character have a significant influence on employee performance. The result of R2 determination coefficient test was 0.442, meaning that the effect of personality character on the employee performance was 44.2%,and the remaining 55.8% was affected by other variables not discussed in this research